Implementasi Islamic Corporate Social Responsibility (CSR) Pada PT. Bumi Lingga Pertiwi di Kabupaten Gresik - Indra Kharisma; Imron Mawardi (Jurnal Ekonomi Syariah Teori dan Terapan, 2014)
Implementation of Corporate Social Responsibility (CSR) is used later to improve the image of the company and its business existence. Instead of CSR to empower people its delude people with a profit motive. Islamic CSR is that CSR refers to business practices that have an ethical responsibility Islamically, companies incorporate Islamic norms characterized by sincerity commitment in maintaining the social contract in its business practices in halal lawful. This study aimed to reveal the implementation of Islamic CSR PT. Bumi Lingga Pertiwi Gresik.This study used a qualitative approach with descriptive case study method. The selections of informant are using purposive sampling method. Data collection was conducted by semi-structured interviews and documentation. Analysis of the data using descriptive method.The results of this study indicate that PT. Bumi Lingga Pertiwi has implemented Islamic CSR based on unity, caliphate, justice and broterhood by creating and running a cooperation agreement in accordance with sharia corridor, provide good service to customers, act fairly and avoid discrimination, provide assistance to the poor in the villages around, helping the development of education and worship, as well as participate protecting the environment by way of planting trees together. REFERENCESAlgifari. 1997. Analisis Statistik Untuk Bisnis dengan Regresi, Korelasi, dan Nonparametrik. Edisi Pertama. Yogyakarta: BPFE-YOGYAKARTA. ---------. 2000. Analisis Regresi Teori, Kasus, dan Solusi. Edisi Kedua. Yogyakarta: BPFE-YOGYAKARTA.Al-Qur’an dan terjemahannya. 2005. Tim Disbintalad. Jakarta: Sari AgungAnogoro, Panji dan Ninik Widiyanti. 1990. PSIKOLOGI DALAM PERUSAHAAN. Cetakan pertama. Jakarta : RINEKA CIPTAAnoraga, Panji. 2006. Psikologi Kerja. Cetakan keempat. Jakarta: Rineka CiptaAnshori, Muslich & Sri Iswati. 2009. Metode Penelitian Kuantitatif. Cetakan pertama. Surabaya: Airlangga University Press.Arikunto, Suharsimi. 2010. Prosedur Penelitian Suatu Pendekatan Praktik. Jakarta: Rineka Cipta.As’ad, Moch. 1998. Seri Ilmu Sumber Daya Manusia: Psikologi Industri. Liberty : Yogyakarta.Azwar, Saiffudin. 1997. Sikap Manusia Teori dan Pengukurannya. Yogyakarta: Pustaka Pelajar.A. Mas’adi, Ghufron. 2002. Fiqh Muamalah Kontekstual. Jakarta: Raja Grafindo.Chablullah, Wibisono. Pengaruh Motivasi Spiritual terhadap Kinerja Karyawan. 2002.Ghani, M. Abdul. 2005.The Spirituality in Business. cetakan pertama. Jakarta: Pena Pundi Aksara.Ghazali, Imam. 2005. Aplikasi Multivariate dengan Program SPSS. Edisi ketiga. Semarang: Undip.Gibson, Ivancevich & Donnelly. 1996. Organization: Behaviour, Structure, Process. Alih Bahasan Djarkasih. Edisi Kelima. Jakarta: Erlangga.Hamid Mursi, Abdul. 1997. SDM Yang Produktif pendekatan Al-Qur’an dan sains. Jakarta: Gema Insani Press.Handoko, T. Hani. 1991. Manajemen. Yogyakarta: BPFE-UGM.Hasibun, Malayu SP. 1994. Manajemen Sumber Daya Manusia Dasar dan Kunci Keberhasilan. Cetakan keenam. Jakarta: Haji Masagung.Indriantoro, Nur dan Bambang Supomo. 1999. Metodologi Penelitian Bisnis untuk Akuntansi dan Manajemen. Edisi Pertama. Yogyakarta: BPFE.Ismail Yusanto, Muhammad dan Muhammad Karebet Widjajakusuma. 2002. Menggagas Bisnis Islami. Jakarta: Gema Insani.Johan, Rita. Kepuasan Kerja Karyawan Dalam Lingkungan Institusi Pendidikan. 2002.LPPM. 1994. Manajemen Perilaku dalam Organisasi. Jakarta: LPPM.Luthans, F. 2005. Organizational Behavior. Mc Graw-Hill Book CoSingapore,Singapura.Qurrotul’aini, Aan. Pengaruh Kepuasan Kerja dan Disiplin Kerja Terhadap Kinerja Karyawan Muslim (Studi Kasus di Dedy Jaya Plaza Ketanggungan Brebes). 2011Rusyd, Ibnu. 2002.Bidayatul Mujtahid terjemahan. Cetakan kedua. Jakarta: Pustaka Amani.Solimun. 2002. Structural Equation Modeling Lisrel dan Amos. Malang: Penerbit Universitas Negeri Malang.Sugiyono. 2011. Metode Penelitian Kuantitatif, Kualitatif dan R&D. Edisi keduabelas. Bandung: Alfabeta.Sunyoto, Danang. 2010. Uji KHI Kuadrat dan Regresi untuk Penelitian. Edisi Pertama. Yogyakarta: Graha Ilmu.Swasto, Bambang. 1996. Pengembangan Sumber Daya Manusia Pengaruhnya Terhadap Kinerja dan Imbalan. Cetakan Pertama. Malang: Universitas Brawijaya.Taniredja, Tukiran dan Hidayati Mustafidah. 2011. Penelitian Kuantitatif: Sebuah Pengantar. Bandung: Alfabeta.Tasmara, Toto. 1995. Etos Kerja Pribadi Muslim. Yogyakarta: PT. Dana Bhakti Wakaf.Usman, Husaini. 2010. Manajemen : teori,praktik dan riset pendidikan. edisi ketiga. Jakarta: bumi aksara.Wexley, Kenneth N., & Gary A. Yukl. 1988. Perilaku Organisasi dan Psikologi Personalia. Jakarta: Binarupa Aksara.Wijono, Sutarto. 2010. Psikologi Industri & Organisasi. Cetakan pertama. Jakarta: Kencana Prenada Media Group.